Synthesis, characterization, chiral separa tion and carbon-carbon double bonds reduction of chalcone using phenylsulfonyl hydrazide - Hapipah, M.A. (2014)
Recent study on chalcone derivatives has attracted much attention due to its great interest in pharmacological activities such as potential cytotoxic agents, antimicrobial agents, 'antiviral, anti flammatory, anesthetic, and etc. There are various methods used to synthesize' chalcone. The most common used is Claisen-Schmidt condensation of aldehyde and ketone by base catalysed or acid catalysed. The reactions of substituted chalcones with phenyl sulfonyl hydrazide in ethanol resulted in the reduction of the carbon-carbon double bond of the chalcones.